The determinants of child weight and height in Sri Lanka: A quantile regression approach - Harsha Aturupane; Anil B. Deolalikar; Dileni Gunewardena (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Reducing child malnutrition is a key goal of most developing countries. To combat child malnutrition with the right set of interventions, policymakers need to have a better understanding of its economic, social and policy determinants. While there is a large literature that investigates the determinants of child malnutrition, it focuses almost exclusively on mean effects of these determinants. However, socioeconomic background variables and policy interventions may affect child nutrition differently at different points of the conditional nutritional distribution.
Keywords: D12; D13; I12; O12; 330; child health; child nutrition; malnutrition; child weight; child height; quantile regression; Sri Lanka; Familienökonomik; Kinder; Ernährung; Unterernährung; Sri Lanka